Evaluation of Particle Grain Size of Sand Embankment for Liquefaction Above Peat Against Vibration - Agus Nugroho, Soewignjo; Yusa, Muhamad; Putra, Agus Ika; Satibi, Syawal; Fatnanta, Ferry; Wibisono, Gunawan; Rinaldi, Rinaldi; Hasibuan, Putra S (Journal of Infrastructure and Construction Technology, 2025)
Liquefaction is the transformation of soil into a liquid. The vibrating table in this study moves in a horizontal direction and the opposite manner in a vertical direction utilizing modelling. Acceleration variations of 0.25 g and 0.32 g were employed. The dirt was 10 centimetres thick. The sand clusters were 15 cm thick, with differences in debris gradient size and water surface on the sample. The uniform load that was employed was 40 kg/m2. Examine the drop of the ground surface and the rising of the porous water for signs of liquefaction. A 0.5mm diameter glass pipe was used to measure the porous water pressure. The test findings revealed that with higher acceleration, effective vertical voltage, and porous water ratio values, the rate of particle graduation has a major influence on the occurrence of liquefaction potential. The test results revealed that poorly graduated fine sand experienced maximum effective vertical stress and elevated porous water ratio values (Ru), whereas well-graded sand tended to be more stable.